Distribution, Condition and Gonad Maturity of the Invasive Pacific Oysters (Crassostrea Gigas, Thunberg 1793) in Cimanuk Delta, Indramayu, West Java, Indonesia - Selia Hermawati; Sulistiono Sulistiono; Agustinus M Samosir (Journal Omni-Akuatika, 2017)
Pacific oyster (Crassostrea gigas) is an invasive species which is able to adapt a wide range of environmental conditions. The study was conducted from August to October 2014. Objective of this study was to asses the distribution pattern, condition and gonad maturity length (Lm 50%) of the Pacific oysters in mangrove ecosystem of Cimanuk Delta, Indramayu, West Java, Indonesia.  This study was conducted in two adjacent areas:  Pabean Ilir and Pagirikan subdeltas. The oysters were collected from the estuary, brackish water ponds and the coastal flat, and  observed for their abundance, total length (mm) and weight (g). Morphological and histological methods were used to estimate the gonad maturity stage. Analysis were carried out to estimate distribution pattern and condition factor. According to the study, the Pacific oyster distribution pattern was clumped. The condition factor of the oyster was higher in the brackish water pond and estuary than in the coastal flat.  The Pacific oyster was found in gonad maturity stage (GMS) I – IV. The oyster was hermaprodit protandry and had length maturity (Lm 50%) of 47,46-48,43 mm (male) and 75,27-75,50  mm (female).